2018
DOI: 10.1007/s11751-018-0321-2
|View full text |Cite
|
Sign up to set email alerts
|

Surgical therapy of benign and low-grade malignant intramedullary chondroid lesions of the distal femur: intralesional resection and bone cement filling with or without osteosynthesis

Abstract: Surgical treatment of benign and low-grade malignant intramedullary chondroid lesions at the distal femur is not well analyzed compared to higher-grade chondrosarcomas. Localization at the distal femur offers high biomechanical risks requiring sophisticated treatment strategy, but scientific guidelines are missing. We therefore wanted to analyze a series of equally treated patients with intralesional resection and bone cement filling with and without additional osteosynthesis. Twenty-two consecutive patients c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…They recommended routine internal fixation after the procedure in order to prevent any pathological fracture and increase stabilisation. Omlor et al (10) found that complications were almost twice as high in patients with…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They recommended routine internal fixation after the procedure in order to prevent any pathological fracture and increase stabilisation. Omlor et al (10) found that complications were almost twice as high in patients with…”
Section: Discussionmentioning
confidence: 99%
“…However, there has been a debate about the surgical treatment method for lowgrade chondrosarcomas (LGC), since they are less aggressive and rarely metastasize (4)(5)(6). Intralesional treatment with or without a local adjuvant therapy is a widely preferred surgical method with a low rate of complications and recurrence (5)(6)(7)(8)(9)(10)(11). Although there are different types of local adjuvants, polymethylmethacrylate (PMMA) bone cement is one of the most common local adjuvants used after intralesional curettage (1,8).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…If no concomitant OA was present, current literature would propose observation of enchondromas, intralesional treatment for a low-grade cartilaginous tumor, and wide resection for intermediate and high-grade chondrosarcomas. 10 , 11 This case series presents an approach used at our institution for performing TKA in patients with knee OA and cartilaginous tumors of the ipsilateral distal femur.…”
Section: Discussionmentioning
confidence: 99%
“… 8 - 11 Recently, there has been an increasing trend toward the intralesional treatment of LGC, in terms of “less extensive,” “limited,” or “conservative” surgical treatment. 12 - 15 …”
Section: Introductionmentioning
confidence: 99%